افتراض صحة الأحكام القضائية في قانون المرافعات المدنية – دراسة مقارنة - Hamid Obaid, Lect .Dr. Husam (Basra studies journal, 2025)
This research examines the principle of the presumption of validity of judicial judgments in civil procedural law, viewing it as one of the procedural doctrines that reinforce the stability of judgments and facilitate their enforcement. This presumption means that a judicial decision is regarded as valid and legally effective from the moment it is issued, unless the contrary is proven through legally prescribed avenues of appeal. The study employs an analytical comparative methodology, drawing on the legal frameworks of Iraq, Egypt, Jordan, and France to determine the extent to which this presumption is binding, the limitations that may restrict its application, and the legal effects it produces in relation to enforcement and appeal procedures. The research concludes that the presumption of validity constitutes a relative legal presumption that does not preclude challenging a judgment; however, it grants the judgment provisional enforceability unless a contrary decision is issued. The researcher recommends explicitly incorporating this principle into the Iraqi Code of Civil Procedure and regulating its exceptions to ensure a balanced relationship between the stability of judicial decisions and the safeguards of justice and due process.